Akkermansia muciniphila ameliorates fatty liver through microbiota-derived α-ketoisovaleric acid metabolism and hepatic PI3K/Akt signaling - Chang Liu; Rongrong Ma; Han Li; Xiaohua Pan; He Qian; Tianyi Yang; Yaoqi Tian (iScience)
Summary: Akkermansia muciniphila (Akk) has been shown to improve obesity via gut microbiota, while its effects on modulating gut fungi remain underexplored. This study investigates the effects of Akk on obese mice, focusing on gut fungi, metabolites, and hepatic lipid metabolism. We found that Akk treatment significantly modulated gut fungal diversity, enhanced gut immune responses, and improved fatty liver. Specifically, the abundance of harmful fungi Fusarium decreased. Subsequently, Akk improved hepatic lipid metabolism via the PI3K/Akt pathway, as determined by proteomics analysis. Additionally, an in vitro colonic organoid and microbiota co-culture system confirmed these effects by validating changes in key fungi and metabolites. Crucially, α-ketoisovaleric acid was identified as a pivotal metabolite, as its supplementation significantly improved hepatic lipid metabolism via PI3K/Akt pathway in obese mice. This study highlights Akk’s potential as a therapeutic agent for obesity by modulating gut fungi and identifying α-ketoisovaleric acid as a critical metabolite.